Characterizing Polytobacco Use Trajectories and Their Associations With Substance Use and Mental Health Across Mid-Adolescence. (14th August 2018) - Cho, Junhan; Goldenson, Nicholas I; Stone, Matthew D; McConnell, Rob; Barrington-Trimis, Jessica L; Chou, Chih-Ping; Sussman, Steven Y; Riggs, Nathaniel R; Leventhal, Adam M
Abstract: Background: Polytobacco product use is suspected to be common, dynamic across time, and increase risk for adverse behavioral outcomes. We statistically modeled characteristic types of polytobacco use trajectories during mid-adolescence and tested their prospective association with substance use and mental health problems. Methods: Adolescents ( N = 3393) in Los Angeles, CA, were surveyed semiannually from 9th to 11th grade. Past 6-month combustible cigarette, e-cigarette, or hookah use (yes/no) over four assessments were analyzed using parallel growth mixture modeling to identify a parsimonious set of polytobacco use trajectories. A tobacco product use trajectory group was used to predict substance use and mental health at the fifth assessment. Results: Three profiles were identified: (1) tobacco nonusers ( N = 2291, 67.5%) with the lowest use prevalence (<3%) of all products across all timepoints; (2) polyproduct users ( N = 920, 27.1%) with moderate use prevalence of each product (8–35%) that escalated for combustible cigarettes but decreased for e-cigarettes and hookah across time; and (3) chronic polyproduct users ( N = 182, 5.4%) with high prevalence of each product use (38–86%) that escalated for combustible cigarettes and e-cigarettes. Nonusers, polyproduct users, and chronic polyproduct users reported successively higher alcohol, marijuana, and illicit drug use and ADHD at the final follow-up, respectively. Both tobacco using groups (vs. nonusers) reported greater odds of depression and anxiety at the final follow-up but did not differ from each other. Conclusions: Adolescent polytobacco use may involve a common moderate risk trajectory and a less common high-risk chronic trajectory. Both trajectories predict substance use and mental health symptomology. Implications: Variation in use and co-use of combustible cigarette, e-cigarette, and hookah use in mid-adolescence can be parsimoniously characterized by a small set common trajectory profiles in which polyproduct use are predominant patterns of tobacco product use, which predict adverse behavioral outcomes. Prevention and policy addressing polytobacco use (relative to single product use) may be optimal tobacco control strategies for youth, which may in turn prevent other forms of substance use and mental health problems.